Số hóa hiệu quả quản lý nhân sự: Mô hình khái niệm và ứng dụng - Ngô Diễm, Hoàng; Trần Trọng, Thùy; Trần Kim , Dung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
Technological advances are pushing organizations to enhance their ability to digitize human resource (HR) activities through management software and applications. However, existing frameworks and guidelines are fragmented and inconsistent in administrative mechanisms, leading to theoretical misalignment and ambiguity in practical application. To address this gap, this study analyzes relevant literature and theories to propose an effective conceptual framework for implementing HR management software and applications. The model is built upon the KeeView platform, incorporating comprehensive HR functionalities, enhanced goal management, competency assessment, and payroll development. This study makes significant contributions to both theoretical development and practical applications in human resource management by digitizing HR models and outlining critical functions for effective operational governance.
Keywords: Human management; Competency assessment; Salary; Digitalization; Software